The Travelers. - Pavone, Chris (Random House Inc, 2016)
When a woman with whom he has shared a harmless flirtation shows up at his hotel door with a gun, travel writer and food expert Will Rhodes discovers the real reason his job occasionally requires him to assume different names and deliver mysterious parcels.